IMPLEMENTASI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN KINERJA GURU DI SD GMIH PITU KABUPATEN HALMAHERA UTARA - Tomi - Wowe (JGK (Jurnal Guru Kita), 2021)
Abstract: Implementation of Principal Leadership in Developing Teacher Performance at GMIH Pitu Elementary School, North Halmahera Regency. The purpose of this research is to find out: (1). The description of the implementation of the principal's leadership on the development of teacher performance. (2). To find out the strategies used by the principal in developing teacher performance. (3). To find out the role of the principal in developing teacher performance. This research is to develop teacher performance at the GMIH Pitu Elementary School, when the principal implements in developing performance it has not gone well because what is happening in schools related to current performance there are still negligent teachers, who are then also still apathetic to follow directions from the leadership even Also due to the Covid-19 pandemic. With the Covid19 pandemic, the activities of teachers in developing performance are constrained, because they are required to always follow the Health Protocol, therefore the role of the principal is highly prioritized so that the performance of the teachers can be minimized properly.